Boana albomarginata (SPIX, 1824) (ANURA: HYLIDAE) SPERMATOGENESIS IN A HIGHLAND ATLANTIC FOREST REMNANT IN PERNAMBUCO STATE, NORTHEASTERN BRAZIL - Freitas, Marco Antonio de; Chaves, Márcio Frazão; Dantas, Alexandre Pereira; Medeiros, Maxsuel Silva; Santos, Lindsey Chayene Ferreira dos; Dubeux, Marcos Jorge Matias; Moura, Geraldo Jorge Barbosa de (Revista Nordestina de Zoologia, 2022)
Knowledge on anurans reproductive biology is still incipient in Brazil, and almost totally unknown in northeastern Brazil. Understanding the various aspects of reproductive patterns is essential for determining the population dynamics of this group. Spermatogenesis is an important animal reproduction phase and strongly regulated by environmental conditions in anurans, mainly by the presence of rainfall, that significantly alters temperature and humidity, two extrinsic parameters that control sex hormone release. Here we describe some aspects of the spermatogenesis of Boana albomarginata from a population located in a highland Atlantic Forest remnant in the semiarid northeastern region of Pernambuco state. We sampled 23 individuals bimonthly between October 2017 and October 2019 from a population located in the Brejo dos Cavalos. The results indicate that spermatogenesis in this population is regulated by rainfall, with consistently high level of sperm production before the onset of rainfall. Thus, this population presents rainfall-regulated spermatogenesis.